Operator and Query Progress Estimation in Microsoft SQL Server Live Query Statistics - Lee, Kukjin; König, Arnd Christian; Narasayya, Vivek; Ding, Bolin; Chaudhuri, Surajit; Ellwein, Brent; Eksarevskiy, Alexey; Kohli, Manbeen; Wyant, Jacob; Prakash, Praneeta; Nehme, Rimma; Li, Jiexing; et al. (Proceedings of the ACM SIGMOD International Conference on Management of Data (SIGMOD 2016), 2016)
We describe the design and implementation of the new Live Query Statistics (LQS) feature in Microsoft SQL Server 2016. The functionality includes the display of overall query progress as well as progress of individual operators in the query execution plan. We describe the overall functionality of LQS, give usage examples and detail all areas where we had to extend the current state-of-the-art to build the complete LQS feature. Finally, we evaluate the effect these extensions have on progress estimation accuracy with a series of experiments using a large set of synthetic and real workloads.